A expressão
é equivalente a
A) -1
B) ![\sqrt{2} -2 \sqrt{2} -2](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D+-2)
C) ![\sqrt{2} +2 \sqrt{2} +2](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D+%2B2)
D) ![\sqrt{2} -1 \sqrt{2} -1](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D+-1)
E) ![\sqrt{2} +1 \sqrt{2} +1](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D+%2B1)
Com resolução!
Soluções para a tarefa
Respondido por
0
Resposta:
alternativa D
Explicação passo-a-passo:
operando as duas frações
__2 + √2 - (2 - √2)__ = _2 + √2 - 2 + √2_ = _2√2_ = √2
4 - 2 2 2
então √2 - 1
alternativa D
Perguntas interessantes